The implementation of a network CODASYL-DML interface for the multi-lingual database system. - Emdi, Bulent (1985)
Traditionally, the design and implementation of a conventional database system begins with the selection of a data model, followed by the specification of a model-based data language. An alternative to this traditional approach to database system development is the multi-lingual database system (MLDS). This alternative approach affords the user the ability to access and manage a large collection of databases via several data models and their corresponding data languages. In this thesis we present the specification and implementation of a network CODASYL-DML language interface for the MLDS. Specifically, we present the specification and implementation of an interface which translates CODASYL-DML data language calls into attribute-based data language (ABDL) requests. We describe the software engineering aspects of our implementation and an overview of the four modules which comprise our CODASYL-DML language interface. Approved for public release; distribution is unlimited. Lieutenant (junior grade), Turkish Navy http://archive.org/details/theimplementatio1094521372